Antenatal gastrointestinal anomalies in neonates subsequently found to have alveolar capillary dysplasia. Issue 5 (13th March 2017) - Goel, Dimple; Oei, Ju Lee; Lui, Kei; Ward, Meredith; Shand, Antonia W.; Mowat, David; Gifford, Andrew J.; Loo, Christine
Key Clinical Message: Alveolar capillary dysplasia (ACD) is a rare condition with variable presentation and clinical course. Clinicians should consider this diagnosis in neonates presenting with nonlethal congenital gastrointestinal malformation, a period of well‐being after birth then unremitting hypoxemia and refractory pulmonary hypertension. Lung biopsy and FOXF1 gene testing may help in diagnosis. Abstract : Alveolar capillary dysplasia (ACD) is a rare condition with variable presentation and clinical course. Clinicians should consider this diagnosis in neonates presenting with nonlethal congenital gastrointestinal malformation, a period of well‐being after birth then unremitting hypoxemia and refractory pulmonary hypertension. Lung biopsy and FOXF1 gene testing may help in diagnosis.